2022
DOI: 10.1093/mnras/stac509
|View full text |Cite
|
Sign up to set email alerts
|

The SAMI Galaxy Survey: the difference between ionized gas and stellar velocity dispersions

Abstract: We investigate the mean locally-measured velocity dispersions of ionised gas (σgas) and stars (σ*) for 1090 galaxies with stellar masses log  (M*/M⊙) ≥ 9.5 from the SAMI Galaxy Survey. For star-forming galaxies, σ* tends to be larger than σgas, suggesting that stars are in general dynamically hotter than the ionised gas (asymmetric drift). The difference between σgas and σ* (Δσ) correlates with various galaxy properties. We establish that the strongest correlation of Δσ is with beam smearing, which inflates σg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 208 publications
1
12
0
Order By: Relevance
“…Following Varidel et al (2016) and Oh et al (2022), we compute the projected mean velocity gradient within an elliptical 1𝑅 𝑒 aperture (bottom). RHS: same as LHS, but using LOESS smoothing to highlight colour gradients.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Varidel et al (2016) and Oh et al (2022), we compute the projected mean velocity gradient within an elliptical 1𝑅 𝑒 aperture (bottom). RHS: same as LHS, but using LOESS smoothing to highlight colour gradients.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Barat et al ( 2019) compared rotational and central dispersion of gas and stars in the Sydney-AAO Multi Integral field (SAMI) Galaxy Survey and find a steeper slope for the 𝑆0.5 − log 10 𝑀 * relationship in stars compared to gas kinematics. More recently, Oh et al (2022) showed that the velocity dispersion of the ionised gas tends to be lower than that of the stars in SAMI galaxies, though caution that beam smearing may be playing a role in artificially enhancing differences. As the precursor to stars, cold gas kinematics can also be compared to stellar kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…In J1400, which looks like a spiral galaxies viewed almost face on, we find that average the stars have a larger velocity dispersion than the gas. This could be caused by asymmetric drift, where the velocity dispersion of the stars is increased due to random motions, resulting in a larger velocity dispersion than that of the gas (Oh et al 2022).…”
Section: Spatially Resolved Kinematicsmentioning
confidence: 99%
“…A common feature observed is that the stellar rotation speed is slower than the rotation speed of the gas. This asymmetric drift is caused by the random motions of the stars (Martinsson et al 2013;Oh et al 2022). Galaxy bulges stand out in the stellar kinematics as they typically have a larger velocity dispersion than the stellar disk (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation